Cooperative Farming in North China - Chinn, Dennis L. (Quarterly Journal of Economics, 1980)
A simple linear programming framework is used to simulate various forms of cooperation between representative farms of two villages in prewar China. The results suggest that even though the two farms individually were quite efficient revenue maximizers, significant mutual benefit would result from the formation of an elementary agricultural producers' cooperative. A move to an advanced cooperative in which dividend payments for land brought into the cooperative initially would be eliminated and income distributed solely according to labor contribution, however, would meet with strong resistance because a sizeable income loss would be involved for the farm with the larger initial land endowment.